Effect of active layer deposition temperature on the performance of sputtered amorphous In-Ga-Zn-O thin film transistors - 吴杰 施俊斐 董承远 邹忠飞 陈宇霆 周大祥 胡哲 詹润泽 (Journal of semiconductors, 2014)
The effect of active layer deposition temperature on the electrical performance of amorphous InGaZnO （a-IGZO） thin film transistors （TFTs） is investigated. With increasing annealing temperature, TFT performance is firstly improved and then degraded generally. Here TFTs with best performance defined as ＂optimized-annealed＂ are selected to study the effect of active layer deposition temperature. The field effect mobility reaches maximum at deposition temperature of 150℃ while the room-temperature fabricated device shows the best subthreshold swing and off-current. From Hall measurement results, the carrier concentration is much higher for intentional heated a-IGZO films, which may account for the high off-current in the corresponding TFT devices. XPS characterization results also reveal that deposition temperature affects the atomic ratio and Ols spectra apparently. Importantly, the variation of field effect mobility of a-IGZO TFTs with deposition temperature does not coincide with the tendencies in Hall mobility of a-IGZO thin films, Based on the further analysis of the experimental results on a-IGZO thin films and the corresponding TFT devices, the trap states at front channel interface rather than IGZO bulk layer properties may be mainly responsible for the variations of field effect mobility and subthreshold swing with IGZO deposition temperature.